Answer:
x = -1 , y = -5
Step-by-step explanation:
Solve the following system:
{y = -4 x - 9 | (equation 1)
4 x - y = 1 | (equation 2)
Express the system in standard form:
{4 x + y = -9 | (equation 1)
4 x - y = 1 | (equation 2)
Subtract equation 1 from equation 2:
{4 x + y = -9 | (equation 1)
0 x - 2 y = 10 | (equation 2)
Divide equation 2 by 2:
{4 x + y = -9 | (equation 1)
0 x - y = 5 | (equation 2)
Multiply equation 2 by -1:
{4 x + y = -9 | (equation 1)
0 x+y = -5 | (equation 2)
Subtract equation 2 from equation 1:
{4 x+0 y = -4 | (equation 1)
0 x+y = -5 | (equation 2)
Divide equation 1 by 4:
{x+0 y = -1 | (equation 1)
0 x+y = -5 | (equation 2)
Collect results:
Answer: {x = -1 , y = -5